The Role of Small Business in Ensuring Employment of the Population - Yormatov Ilmidin Toshmatovich (Genius Journals, 2022)
This article talks about the role of small businesses and entrepreneurship in the employment of the population and the importance of private entrepreneurship development in ensuring sustainable economic growth and employment of the population. In this regard, as a continuation of the activities aimed at revitalizing economic reforms and further supporting business entities, the open dialogue held by the President of the Republic of Uzbekistan Sh.M. Mirziyoev with entrepreneurs in August 2022 is the basis for further development of this sector. created significant importance in raising the economic and social development of the country to a new, higher level.
Keywords: small business; entrepreneurship; population employment